Reproductive choices among HIV positive patients in Ekurhuleni District, Gauteng province - Agbo, Samuel Onoja (My University, 2014)
Background There is now global recognition of the reproductive health rights of all individuals, including people living with HIV (PLHIV). These include inter alia, decisions on the number, spacing and timing of their children. In light of limited information on the reproductive choices of PLHIV at primary health care (PHC) level, the aim of this research study was to develop new knowledge on the reproductive concerns and desires of PLHIV and to determine current services provided for HIV positive individuals in the Ekurhuleni district of Gauteng Province. Methods A cross-sectional study design was used to explore the reproductive choices and the factors influencing these choices among HIV positive patients in the Ekurhuleni district. During 2013, a random sample of HIV positive patients attending community health centres was selected. After informed consent was obtained, trained fieldworkers administered a structured questionnaire that elicited information on socio-demographics, reproductive choices, and knowledge on available reproductive services. Survey data were analysed using STATA version 13. Results The majority of survey participants (n=430) were female (70%) and unemployed (57 %). The mean age of participants was 36 years (SD 8.6): 40.8 years (SD 8.7) for men and 34.5 years (SD7.8) for women. The expressed desire for children was 46% (95% CI: 41.4 – 50.9). In the multiple logistic regression analysis, predictors of desire for children were: age less than 49, marriage or living together, and no biological children. The odds of wanting children was 51.5 [95% CI: 14.8–178.8] times higher for those without children, compared to those with two or more children, while for those less than 25 years, the odds of wanting children was 22.0 [95% CI: 1.9-254] compared to those older than 50 years. Conclusion PHC clinics and health care providers should be capacitated to address the reproductive health needs of PLHIV, and these needs should be reflected in provincial and national policies.
Keywords: Family Planning Services; HIV